2005
DOI: 10.1007/s00441-004-1016-1
|View full text |Cite
|
Sign up to set email alerts
|

Standard three-dimensional glomeruli of the Manduca sexta antennal lobe: a tool to study both developmental and adult neuronal plasticity

Abstract: The metamorphosing antennal lobe (AL) of the sphinx moth Manduca sexta serves as an established model system for studying neuronal development. To improve our understanding of mechanisms involved in neuronal plasticity, we have analyzed the size, shape, and localization of ten identified glomeruli at three different time points during development and in the adult, viz., (1) 13 days after pupal eclosion (P13), which reflects a time when the basic glomerular map has formed, (2) immediately after adult eclosion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 71 publications
4
75
0
Order By: Relevance
“…moths), in which glomerular development mostly occurs during the pupal and early adult stages [7,9], cockroach glomeruli continually develop in each molting after hatching concurrent with the growth of the antenna [15,18,19]. Histological studies have suggested that the MGC of the cockroach is formed during the last third of postembryonic development by fusion of several small glomeruli [15].…”
Section: Abstract (Within 250 Words)mentioning
confidence: 99%
See 1 more Smart Citation
“…moths), in which glomerular development mostly occurs during the pupal and early adult stages [7,9], cockroach glomeruli continually develop in each molting after hatching concurrent with the growth of the antenna [15,18,19]. Histological studies have suggested that the MGC of the cockroach is formed during the last third of postembryonic development by fusion of several small glomeruli [15].…”
Section: Abstract (Within 250 Words)mentioning
confidence: 99%
“…In the hawkmoth, glomerulus development depends on the arrival of a subset of sensory axons, and this occurs at different times for different glomeruli during the pupal stage [9]. However, two adjacent male-specific macroglomeruli (called "cumulus" and "toroid") have similar glomerular volumes and grow at similar rates, at least in their late developmental phases [7].…”
Section: Abstract (Within 250 Words)mentioning
confidence: 99%
“…After fixation, brains were either embedded in gelatin/albumin, postfixed overnight in 4% buffered formaldehyde and cut at 40 lm with a vibrating blade microtome (Leica VT 1000S) in the frontal, sagittal or horizontal plane, or processed as wholemount. Immunostaining procedure was performed exactly as described in Schachtner et al (2004b) or, for the wholemounts, as described in Huetteroth and Schachtner (2005). For triple-labeling, the anti-Mas-AT, anti-GABA, and antisynapsin antibodies were applied simultaneously and, likewise, the corresponding secondary antisera.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Digitization and 3D reconstructions of wholemount ALs labeled with anti Mas-AT and anti-synapsin antisera, visualized by corresponding secondary antisera coupled to Cy2 and Cy5, respectively, were performed with the Leica TCS SP2 and the 3D reconstruction software AMIRA 3.1-4.1.1 (Mercury Computer Systems, Chelmsford, MA) according to the protocol described in Huetteroth and Schachtner (2005). The AL outlines and cell group borders were labeled based on background staining of either data channel.…”
Section: D-reconstructionmentioning
confidence: 99%
See 1 more Smart Citation